DISTRIBUSI TEGANGAN PADA PERCABANGAN PIPA 90O AKIBAT TEKANAN INTERNAL MENGGUNAKAN MEH - Agus Suprihanto; Djoeli Satrijo; Dwi Basuki Wibowo (TEKNIK, 2007)
Piping system is very important in many industries. Ones of crucial in design of piping system are todetermine the stress distribution around the branch. In this research, the distributed stress over 90o branchpiping system was evaluated with finite element method. Five models piping 90o branch which differentratio of diameter of pipe have been developed. The load applied on the models is internal pressure.The results indicate that around the branch there is stress distribution. The maximum stress is located atcenter of the branch but decrease significantly in the distance 30mm-45mm from it. Beyond the distance75mm from center, for diameter ratio 1, the model gives good agreement with experiment data